Economic development : past and present - Gill, Richard T. (Englewood Cliffs, N.J., Prentice-Hall, 1973)
This book provides an introduction to economics using a historical approach with topics like: factors in economic development; approaches to the theory of development; beginning of growth in the economically advanced countries; the growth of the American economy; the problems of the less developed countries; development in process-India and China.
Includes bibliographical references: p. 132-133.
lje 26/04/2018, ijb 08/04/2019
Loans
Keywords: Economic development; Developing countries